Exploring The Role Of Teachers In The Development Of Hidden Curriculum Based On Islamic Boarding Schools - Bachrul Ulum; Riswadi Riswadi (AL-WIJDÃN Journal of Islamic Education Studies, 2023)
The most effective effort in achieving the national development target is through education. The purpose of this study is to explore the role of teachers in the development of hidden curriculum-based islamic boarding schools. This research uses a qualitative approach method with data collection techniques in the form of interviews and observations. The subject of the study consisted of 80 students and 10 teachers. Findings from the study show that teachers have a very crucial role in the development of hidden curricula based on islamic boarding schools, especially in terms of shaping the character of students. Teachers understand that the character of students is not only formed through formal subjects but also the values of Islamic boarding schools passed down from generation to generation. Therefore, the teacher acts as a facilitator in helping students understand and apply the values of Islamic boarding schools in everyday life. Teachers also act as models for students, by demonstrating behaviors and actions that are following the values of Islamic boarding schools. In this case, teachers need to have a deep understanding of the values of Islamic boarding schools and the ability to integrate these values into the existing curriculum.  Keywords: Teacher, Hidden Curriculum, Islamic Boarding School, Student Character.